PERAN ORANG TUA MENGATASI PERILAKU ANAK DALAM PEMANFAATAN MEDIA SOSIAL SELAMA PANDEMI COVID-19 DI DUSUN ARJOSARI AMPELGADING MALANG - Muslimah Muslimah; Chalimatus Sa’diyah; Moh. Eko Nasrulloh (VICRATINA, 2021)
The development of the times affects human life in various fields, one of which is the social field. This development has a negative impact, such as a lack of attention and supervision from parents to monitor the child's development. This can be seen from the morals of children who are familiar with social media, their behavior is getting less good. Based on the initial observations made by the researchers, there were some children in Arjosari Hamlet who experienced changes in behavior such as being lazy, ignoring parental orders, and not focusing on learning. In this study, researchers used a qualitative approach, data collection using the method of observation, interviews and documentation. The research location is in Arjosari Hamlet, Ampelgading Village, Malang Regency. In this study, researchers found several forms of parental roles in overcoming children's behavior in the use of social media, such as accompanying children online, limiting and supervising the use of gadgets or social media, communication, more attention, and good examples. The supporting factor for this problem is the role of both parents, namely the teacher and parental discipline, while the inhibiting factors are time constraints, lack of communication, and dishonesty of children.